MD or not MD - Arno Zaritsky; A. James Beyer (Critical Care Medicine, 1992)
Background Individuals with compromised immune systems, particularly those living with human immunodeficiency virus (HIV), face an elevated risk of opportunistic fungal infections (OFIs), including candidiasis and cryptococcal meningitis. This systematic review and meta-analysis aimed to determine the pooled prevalence of OFIs among HIV-positive individuals across different regions of Ethiopia. Methods English-language articles were identified through a comprehensive search of online databases, including ScienceDirect, PubMed, and Cochrane Library. The Joanna Briggs Institute critical appraisal tool for prevalence studies was used to assess study quality. Heterogeneity and publication bias were evaluated using inverse variance (I2 statistic), sensitivity analysis, funnel plots, and Egger's regression test. Due to significant heterogeneity, a random-effects model was employed to estimate the pooled prevalence of OFIs among HIV-positive individuals. Data analysis was conducted using STATA version 14. This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines, and the protocol was registered in the International Prospective Register of Systematic Reviews (CRD42024620835). Results From 254 initially identified articles, 19 studies on Candida (8482 participants) and 9 studies on Cryptococcus (4017 participants) met the inclusion criteria. The pooled prevalence of candidiasis was 13.46% (95% confidence interval: 8.54-18.39), while cryptococcal meningitis had a prevalence of 3.15% (95% confidence interval: 1.59-4.71). Conclusion To reduce the burden of OFIs in HIV-positive individuals, implementation of the following measures is critical: early HIV testing and rapid initiation of antiretroviral therapy, promotion of improved hygiene practices, and development of enhanced diagnostic tools coupled with prompt treatment of OFIs. These interventions are essential for improving clinical outcomes and reducing morbidity in this vulnerable population.